20 Armoured Infantry Brigade downgrade study: epidemiology of principal conditions and plugging leaks in the rehabilitation pipeline. Issue 5 (2nd February 2019) - Papworth, James; Osborne, L; Shimmings, M A; Roberts, C C S
Abstract : Introduction: In April 2017, 22% of Army Full-time Trade Trained Strength was downgraded, reducing fully deployable strength to 60 546, against a target of 82 000. In June 2017, Commander 20 Armoured Infantry Brigade (20 AI Bde) initiated a study to look at the principal conditions causing medical downgrading, as a stepping stone to finding ways of reducing injury, enhancing rehabilitation and improving deployability. Method: The Defence Medical Information Capability Programme medical records for every downgraded soldier in 20 AI Bde and supporting units were scrutinised to identify their Medical Deployment Standard and the primary condition causing downgrading. Results: A total of 842 downgraded soldiers were identified from a held strength of 3827 personnel. Sixty-five per cent of these downgrades were due to musculoskeletal injury (MSKI). Of this 65%, the majority were due to knee (31%), spine (28%) and foot/ankle (23%). Of the remaining 35%, the majority were due to noise-induced hearing loss (NIHL) (22%), adjustment disorders (19%) and non-freezing cold injury (NFCI) (13%). Several factors that slowed an individual's recovery pathway were identified. They mainly relate to soldiers being lost to follow-up through lack of active case management. Conclusions: MSKI is responsible for most downgraded personnel at Brigade level. The distribution of principal conditions is similar to previous studies looking at recruits and individual units. The creation of a rehabilitation troop, delivering active case management, can reduce the number of soldiers leaking out of the rehabilitation pipeline.